Occult Vancomycin-Resistant Enterococcus faecium ST117 Displaying a Highly Mutated vanB2 Operon - Antonella Santona; Elisa Taviani; Maura Fiamma; Massimo Deligios; Hoa M. Hoang; Silvana Sanna; Salvatore Rubino; Bianca Paglietti (Antibiotics, 2023)
Rare information is available on clinical Enterococcus faecium encountered in Sardinia, Italy. This study investigated the antimicrobial susceptibility profiles and genotypic characteristics of E. faecium isolated at the University Hospital of Sassari, Italy, using the Vitek2 system and PCR, MLST, or WGS. Vitek2 revealed two VanB-type vancomycin-resistant Enterococcus faecium (VREfm) isolates (MICs mg/L = 8 and ≥32) but failed to detect vancomycin resistance in one isolate (MIC mg/L ≤ 1) despite positive genotypic confirmation of vanB gene, which proved to be vancomycin resistant by additional phenotypic methods (MICs mg/L = 8). This vanB isolate was able to increase its vancomycin MIC after exposure to vancomycin, unlike the “classic” occult vanB-carrying E. faecium, becoming detectable by Vitek 2 (MICs mg/L ≥ 32). All three E. faecium had highly mutated vanB2 operons, as part of a chromosomally integrated Tn1549 transposon, with common missense mutations in VanH and VanB2 resistance proteins and specific missense mutations in the VanW accessory protein. There were additional missense mutations in VanS, VanH, and VanB proteins in the vanB2-carrying VREfm isolates compared to Vitek2. The molecular typing revealed a polyclonal hospital-associated E. faecium population from Clade A1, and that vanB2-VREfm, and nearly half of vancomycin-susceptible E. faecium (VSEfm) analyzed, belonged to ST117. Based on core genome-MLST, ST117 strains had different clonal types (CT), excluding nosocomial transmission of specific CT. Detecting vanB2-carrying VREfm isolates by Vitek2 may be problematic, and alternative methods are needed to prevent therapeutic failure and spread.